2024
DOI: 10.3389/fcell.2024.1357862
|View full text |Cite
|
Sign up to set email alerts
|

Neural conditional ablation of the protein tyrosine phosphatase receptor Delta PTPRD impairs gliogenesis in the developing mouse brain cortex

Francisca Cornejo,
Nayhara Franchini,
Bastián I. Cortés
et al.

Abstract: Neurodevelopmental disorders are characterized by alterations in the development of the cerebral cortex, including aberrant changes in the number and function of neural cells. Although neurogenesis is one of the most studied cellular processes in these pathologies, little evidence is known about glial development. Genetic association studies have identified several genes associated with neurodevelopmental disorders. Indeed, variations in the PTPRD gene have been associated with numerous brain disorders, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 77 publications
(170 reference statements)
0
0
0
Order By: Relevance
“…What accounts for the increase in glutamatergic neurons in adult Ptprd-/- mice? We propose that it is directly related to the increase in Tbr2-positive intermediate precursor cells in these mice during embryogenesis that we previously reported [ 11 , 12 ]. There is abundant evidence that ASD-associated genes exhibit cell cycle changes in neural precursor cells during brain development, culminating in an alteration in the total number of glutamatergic neurons [ 48 ].…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…What accounts for the increase in glutamatergic neurons in adult Ptprd-/- mice? We propose that it is directly related to the increase in Tbr2-positive intermediate precursor cells in these mice during embryogenesis that we previously reported [ 11 , 12 ]. There is abundant evidence that ASD-associated genes exhibit cell cycle changes in neural precursor cells during brain development, culminating in an alteration in the total number of glutamatergic neurons [ 48 ].…”
Section: Discussionmentioning
confidence: 52%
“…Mutations or aberrant expression of this gene have previously been associated with various neurodevelopmental disorders such as obsessive-compulsive disorder, schizophrenia, and ASD [ 14 ]. In this regard, we reported that Ptprd is a key regulator of mouse embryonic neurogenesis, controlling the numbers of neurogenic intermediate progenitor cells and, ultimately, the number of neonatal cortical neurons [ 11 , 12 ]. Here, we found that the developmental increase of excitatory neurons persisted through adulthood, affecting excitatory synaptic function in the mPFC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations